HUBUNGAN KEKUATAN OTOT LENGAN BAHU DAN KELENTUKAN OTOT PUNGGUNG TERHADAP KEMAMPUAN LEMPAR LEMBING PADA ATLET PPLP PUTRA DISPORA RIAU - Muslima, Muslima; Zainur, zainur; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine whether there is a relationship between shoulder arm muscle strength and back muscle flexibility on javelin throwing ability in PPLP athletes Putra Dispora Riau. The sample from this study were 6 javelin throwing athletes. The sampling technique was taken (total sampling) or full sampling technique in PPLP Putra Dispora Riau javelin throwing athletes, amounting to 6 people. The results of the correlation in PPLP Putra Dispora Riau javelin athlete where the first analysis between shoulder arm strength X1 and Y where rtab at a significant level É‘ (0.05) = r_count (0.984) <r_tab (0.878), means the hypothesis is accepted and there is a moderate relationship between shoulder arm strength to javelin throwing ability at PPLP athletes Putra Dispora Riau. From the calculation of the analysis of both X2 and Y, where r_tab is at a significant level É‘ (0.05) = r_count (0.984) <r_tab (0.878), it means that the hypothesis is accepted and there is a moderate relationship between back muscle flexibility to javelin throwing ability at PPLP Putra Dispora Riau . The third analysis of the relationship of shoulder arm muscle strength (X1) back muscle flexibility (X2) with javelin throwing ability (Y) where rtab at a significant level É‘ (0.05) = r_count (0.984) <r_tab (0.878), it can be concluded that the relationship between ( X1) and (X2) with (Y) or the relation of shoulder arm muscle strength and back muscle flexibility to javelin throwing ability in PPLP Putra Dispora Riau athletes on moderate intervention.Key Words: Shoulder Arm Muscle Strength, Flexibility and Throwing.